The effectiveness of using teacher’s E-Portfolio Evaluation in the development of academic achievement and performance skills with the computer course of the first year secondary industrial students - El Sakhawy, Abdel Monsef Saad Mohamed (Arab Journal for Sciences and Research Publishing, 2016)
This research aims to measure the effectiveness of using teacher’s E-Portfolio Evaluation in the development of academic achievement and performance skills with the computer course of the first year secondary industrial students. To reach this goal a list of goals was determined for the Word program course classified into knowledge vocabularies and skill vocabularies and each general goal has a set of sub-goals and a script of the Teacher E-Portfolio was done following the model of Helen Barrett (2006) for instructional design. The researcher used the descriptive approach to monitor and analysis the studies and literature related to the research theoretical framework, its terms procedural limitations and the quasi-experimental approach in the research experience (test) by quasi-experimental design to measure the effectiveness of the valuation by using the teacher’s E-Portfolio in the development of computer course academic achievement and skills performance with the first year secondary industrial students. The researcher chose a sample of (50) students randomly from the industrial secondary first year students of Shobrakhitt industrial secondary school for boys, Al-Beheira governorate (Arab Republic of Egypt). The sample of the research was divided into two groups, the first group (experimental), which is considering Microsoft Word 2003Course via the teacher’s e-portfolio and the valuation of the electronic tests are through the teacher’s e-portfolio estimated (25) students and the dominant group studies in the traditional way estimated (25) students. The researcher prepared the research tools: Pre/ after achievement test to measure the cognitive aspect associated with the skills to deal with Microsoft Word 2003 for the first-grade industrial secondary students in computer course. (Prepared by the researcher). Note card to measure the skills of dealing with Microsoft Word 2003 the first-grade industrial secondary students in computer course. (Prepared by the researcher). The research has come to the following results: The very large impact of efficiency on Evaluation by using the teacher’s E-portfolio in the development of academic achievement and skill performance for the computer course with the first year industrial secondary students.